KÓP VEKTORLÍ QATNASÍW TIYKARÍNDA DIFFERENCIYALASQAN INKLYUZIVLI BILIMLENDIRIW: QARAQALPAQ MEKTEPLERINDE QOLLANÍLÍWÍ - Pirniyazova, Gulchira Nietbaevna (SCIENCE and SOCIETY, 2026)
The article highlights the importance of the principles of differentiation based on a multi-vector approach in the inclusive education system. In particular, the mechanisms for ensuring an individual approach in general education schools of Karakalpakstan and creating educational conditions that meet the needs of students are analyzed. The practical importance of the principles of equality, personalization and pedagogical adaptation in education is substantiated.